Consensus guidelines for the management of adult immune thrombocytopenia in Australia and New Zealand. Issue 1 (10th October 2021) - Choi, Philip YI; Merriman, Eileen; Bennett, Ashwini; Enjeti, Anoop K; Tan, Chee Wee; Goncalves, Isaac; Hsu, Danny; Bird, Robert
Abstract: Introduction: The absence of high quality evidence for basic clinical dilemmas in immune thrombocytopenic purpura (ITP) underlines the need for contemporary guidelines relevant to the local treatment context. ITP is diagnosed by exclusions, with a hallmark laboratory finding of isolated thrombocytopenia. Main recommendations: Bleeding, family and medication histories and a review of historical investigations are required to gauge the bleeding risk and possible hereditary syndromes. Beyond the platelet count, the decision to treat is affected by individual bleeding risk, disease stage, side effects of treatment, concomitant medications, and patient preference. Treatment is aimed at achieving a platelet count > 20 × 10 9 /L, and avoidance of severe bleeding. Steroids are the standard first line treatment, with either 6‐week courses of tapering prednisone or repeated courses of high dose dexamethasone providing equivalent efficacy. Intravenous immunoglobulin can be used periprocedurally or as first line therapy in combination with steroids. Changes in management as a result of this statement: There is no consensus on choice of second line treatments. Options with the most robust evidence include splenectomy, rituximab and thrombopoietin receptor agonists. Other therapies include azathioprine, mycophenolate mofetil, dapsone and vinca alkaloids. Given that up to one‐third of patients achieve a satisfactory haemostatic response, splenectomy should be delayed for at least 12 months if possible. In life‐threatening bleeding, we recommend platelet transfusions to achieve haemostasis, along with intravenous immunoglobulin and high dose steroids.